AMI SZ observations and Bayesian analysis of a sample of six redshift-one clusters of galaxies - Schammel, M.; Feroz, F.; Grainge, K.; Hobson, M.; Hurley-Walker, Natasha; Lasenby, A.; Olamaie, M.; Perrott, Y.; Pooley, G.; Rodriguez-Gonzalvez, C.; Rumsey, C.; Saunders, R.; et al. (Oxford University Press, 2013)
We present 16-GHz Sunyaev–Zel’dovich observations using the Arcminute Microkelvin Imager (AMI) and subsequent Bayesian analysis of six galaxy clusters at redshift z ˜ 1 chosen from an X-ray- and infrared-selected sample from Culverhouse et al. In the subsequent analysis, we use two cluster models, an isothermal ß-model and a Dark Matter Generalised Navarro-Frenk-White (DM-GNFW) model in order to derive a formal detection probability and the cluster parameters. We detect two clusters (CL J1415+3612 and XMJ 0830+5241) and measure their total masses out to a radius of 200 times the critical density at the respective cluster’s redshift. For CL J1415+3612, we find MT,200 = 7.3+1.8 -1.8 × 1014M (ß-model) and MT,200 = 10.42.5 -2.4 × 1014M (DM-GNFW model) and for XMJ0830+5241, we find MT,200 = 3.6+1.1 -1.1 × 1014M, (ß-model) and MT,200 = 4.7+1.4 -1.4 × 1014M (DM-GNFW model), which agree with each other for each cluster. We also present maps before and after source subtraction of the entire sample and provide 1D and 2D posterior marginalized probability distributions for each fitted cluster profile parameter of the detected clusters. Using simulations which take into account the measured source environment from the AMI Large Array (LA), source confusion noise, cosmic microwave background primordials, instrument noise, we estimate from small-radius (r2500) X-ray data from Culverhouse et al., the detectability of each cluster in the sample and compare it with the result from the Small Array (SA) data. Furthermore, we discuss the validity of the assumptions of isothermality and constant gas mass fraction.We comment on the bias that these small-radius estimates introduce to large-radius SZ predictions. In addition, we follow-up the two detections with deep, single-pointed LA observations.We find a 3s tentative decrement towards CL J1415+3612 at high resolution and a 5s high-resolution decrement towards XM J0830+5241.